Label-Free Characterization and Quantification of Mucosal Inflammation in Common Murine Colitis Models With Multiphoton Imaging - Kreiß, Lucas; Thoma, Oana-Maria; Lemire, Sarah; Lechner, Kristina; Carlé, Birgitta-Elisabeth; Dilipkumar, Ashwathama; Kunert, Timo; Scheibe, Kristina; Heichler, Christina; Merten, Anna-Lena; Weigmann, Benno; Neufert, Clemens; et al. (Inflammatory Bowel Diseases, 2022)
Background Clinical challenges in inflammatory bowel diseases require microscopic in vivo evaluation of inflammation. Here, label-free imaging holds great potential, and recently, our group demonstrated the advantage of using in vivo multiphoton endomicroscopy for longitudinal animal studies. This article extends our previous work by in-depth analysis of label-free tissue features in common colitis models quantified by the multiphoton colitis score (MCS). Methods Fresh mucosal tissues were evaluated from acute and chronic dextran sulfate sodium (DSS), TNBS, oxazolone, and transfer colitis. Label-free imaging was performed by using second harmonic generation and natural autofluorescence. Morphological changes in mucosal crypts, collagen fibers, and cellularity in the stroma were analyzed and graded. Results Our approach discriminated between healthy (mean MCS = 2.5) and inflamed tissue (mean MCS > 5) in all models, and the MCS was validated by hematoxylin and eosin scoring of the same samples (85.2% agreement). Moreover, specific characteristics of each phenotype were identified. While TNBS, oxazolone, and transfer colitis showed high cellularity in stroma, epithelial damage seemed specific for chronic, acute DSS and transfer colitis. Crypt deformations were mostly observed in acute DSS. Conclusions Quantification of label-free imaging is promising for in vivo endoscopy. In the future, this could be valuable for monitoring of inflammatory pathways in murine models, which is highly relevant for the development of new inflammatory bowel disease therapeutics.
CRIS-Team WoS Importer:2022-10-07

Natural NADH and FAD Autofluorescence as Label-Free Biomarkers for Discriminating Subtypes and Functional States of Immune Cells - Lemire, Sarah; Thoma, Oana-Maria; Kreiß, Lucas; Völkl, Simon; Friedrich, Oliver; Neurath, Markus; Schürmann, Sebastian; Waldner, Maximilian (International Journal of Molecular Sciences, 2022)
Immune cell activity is a major factor for disease progression in inflammatory bowel diseases (IBD). Classifying the type and functional state of immune cells is therefore crucial in clinical diagnostics of IBD. Label-free optical technologies exploiting NADH and FAD autofluorescence, such as multiphoton microscopy, have been used to describe tissue morphology in healthy and inflamed colon samples. Nevertheless, a strategy for the identification of single immune cell subtypes within the tissue is yet to be developed. This work aims to initiate an understanding of autofluorescence changes depending on immune cell type and activation state. For this, NADH and FAD autofluorescence signals of different murine immune cell subtypes under native conditions, as well as upon in vitro stimulation and cell death, have been evaluated. Autofluorescence was assessed using flow cytometry and multiphoton microscopy. Our results reveal significantly increased NADH and FAD signals in innate immune cells compared to adaptive immune cells. This allowed identification of relative amounts of neutrophils and CD4+ T cells in mixed cell suspensions, by using NADH signals as a differentiation marker. Furthermore, in vitro stimulation significantly increased NADH and FAD autofluorescence in adaptive immune cells and macrophages. Cell death induced a significant drop in NADH autofluorescence, while FAD signals were hardly affected. Taken together, these results demonstrate the value of autofluorescence as a tool to characterize immune cells in different functional states, paving the way to the label-free clinical classification of IBD in the future.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Cell autofluorescence; FAD; Flow cytometry; Immune cells; Inflammatory bowel diseases; Multiphoton microscopy; NADH